Iodine–Starch test for assessment of hyperhidrosis in amputees, evaluation of different methods of application*. Issue 25 (4th December 2018) - Hansen, Colby; Wayment, Ben; Klein, Stephanie; Godfrey, Bradeigh
Abstract: Purpose: Hyperhidrosis is a common problem for amputees. The iodine–starch test is frequently used to assess hyperhidrosis, but a method for its application has not been described for amputees. Methods: We performed an unblinded comparison of the iodine–starch test using various methods to protect the prosthesis in 10 prosthetic limb users with hyperhidrosis. Results: Plastic wrap produced a diffuse pattern of sweating in 70% of subjects. Forty percent had complaints about this method, and 50% experienced leakage of iodine stain onto prosthetic liners. The prosthetic sheath produced a focal or multifocal reaction in 100% of subjects after 10 min of ambulation. Eighty percent had minor leakage onto the liner, and complaints were noted in 10%. The proportion that experienced diffuse sweating was significantly higher in the plastic wrap condition ( p  = 0.016; difference in proportions = 70%; 95% confidence interval = 32–100%). The prosthetic sock was tested in four subjects and all had at least mild complaints; three had minor leakage onto the liner. Repeated complaints and lack of stain prevention led to discontinuation with this method. Conclusions: Of the three methods, the sheath produces a focal or multifocal reaction after 10 min of ambulation and tends to cause less subject complaints. It should be the preferred method to apply the iodine–starch test to amputees. Implications for rehabilitation: Hyperhidrosis is a common problem in amputees which negatively affects quality of life. The iodine–starch test is commonly used to guide treatment decisions for hyperhidrosis, but a preferred method for applying it in amputees has not been described. This study describes different methods for applying the iodine–starch test. A prosthetic sheath covering should be the preferred method for the iodine–starch test in amputees.